2023
DOI: 10.1002/cplu.202200423
|View full text |Cite
|
Sign up to set email alerts
|

MXenes Functionalized with Macrocyclic Hosts: From Molecular Design to Applications

Abstract: Two‐dimensional (2D) MXene has aroused wide attention for its excellent physical and chemical properties. The interlayer engineering formed by layer‐by‐layer stacking of MXene nanosheets can be employed for molecular sieving and water purification by incorporating specific groups onto the exterior surface of MXene. Macrocyclic hosts exhibiting unique structural features and recognition ability can construct smart devices for external stimuli with reversible features between macrocycles and guests. On that basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 99 publications
(133 reference statements)
1
10
0
Order By: Relevance
“…44,45,48,49 Intercalation of crown-ethers and cryptands first achieved with 2:1 charged silicates was later on applied to other 2D host lattices, such as hydrated vanadium pentoxide, 50 graphite oxide, 51 layered chalcogenophosphates, 52 iron(III) oxychloride, 53,54 and layered transition metal disulfides, 55,56 and also absorbed by porous carbons, giving rise to hybrid materials. 57 MXenes appear to be excellent candidates for the assembly of macrocyclic compounds and the subsequent formation of interlayer complexes that could be used to improve ionic battery components, electrochemical sensors, and membranes.…”
Section: Hybrid Organic−inorganic Materials From Molecular Intercalat...mentioning
confidence: 99%
See 1 more Smart Citation
“…44,45,48,49 Intercalation of crown-ethers and cryptands first achieved with 2:1 charged silicates was later on applied to other 2D host lattices, such as hydrated vanadium pentoxide, 50 graphite oxide, 51 layered chalcogenophosphates, 52 iron(III) oxychloride, 53,54 and layered transition metal disulfides, 55,56 and also absorbed by porous carbons, giving rise to hybrid materials. 57 MXenes appear to be excellent candidates for the assembly of macrocyclic compounds and the subsequent formation of interlayer complexes that could be used to improve ionic battery components, electrochemical sensors, and membranes.…”
Section: Hybrid Organic−inorganic Materials From Molecular Intercalat...mentioning
confidence: 99%
“…66 These circumstances are comparable to the intercalation of MoS 2 -Li, which delaminated in aqueous dispersion containing 12-crown-4 (12C4), 15crown-5 (15C5), and 18-crown-6 (18C6) crown-ethers as reported by Lara et al 56 However, to date, crown-ethers and cryptands have hardly been explored as host molecules for MXene intercalations and formation of interlayer complexes. A recent paper by Li et al 57 reports on the assembly of diverse macrocycles, including 14C4 and 18C6, which can be attached to the surface of MXenes by electrostatic interactions observing by TEM the changes in the interlayer spacings of these 2D solids. According to these results, there is considerable room for future developments of membrane technology and smart devices, among other applications, in the emerging field of MXenes−macrocyclic compounds, similar to that reported for clay minerals and other 2D host solids.…”
Section: Hybrid Organic−inorganic Materials From Molecular Intercalat...mentioning
confidence: 99%
“…This makes it possible for 2D membranes to be highly selective, while maintaining a mild flux. 17 In recent years, various 2D membrane building blocks, such as graphene oxide (GO), [18][19][20] MXenes, [21][22][23][24] layered double hydroxides (LDH), [25][26][27] metal-organic frameworks (MOFs), [28][29][30] and C 3 N 4 have been reported (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that MXene-based membranes with tunable hydrophilicity are promising candidates for enhanced water purification via the removal of dyes, metal ions, and salts. Silane-grafted MXene membranes have improved water purification performance, and innovative approaches, such as inorganic–organic hybrid membranes, intercalation with pillararene, and functionalization with macrocyclic hosts, have also shown great potential for efficiently removing solute molecules from water. …”
Section: Introductionmentioning
confidence: 99%